2005
DOI: 10.1534/genetics.105.042952
|View full text |Cite
|
Sign up to set email alerts
|

Marker-Based Quantitative Genetics in the Wild?: The Heritability and Genetic Correlation of Chemical Defenses in Eucalyptus

Abstract: Marker-based methods for estimating heritability and genetic correlation in the wild have attracted interest because traditional methods may be impractical or introduce bias via G 3 E effects, mating system variation, and sampling effects. However, they have not been widely used, especially in plants. A regression-based approach, which uses a continuous measure of genetic relatedness, promises to be particularly appropriate for use in plants with mixed-mating systems and overlapping generations. Using this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 58 publications
(61 reference statements)
2
65
2
Order By: Relevance
“…In our study system, molecular data suggest that populations were established by multiple founders (García-Verdugo et al 2010;García-Verdugo et al in review), which enhances a mixture of relatedness within populations and thus favors significant variance (Ritland 2000). In addition, sampled individuals were on average 15-20 m apart, an optimal distance with regard to maximizing actual variance in other woody species (Klaper et al 2001;Andrew et al 2005).…”
Section: Measurement Of Light-related Traitsmentioning
confidence: 78%
See 1 more Smart Citation
“…In our study system, molecular data suggest that populations were established by multiple founders (García-Verdugo et al 2010;García-Verdugo et al in review), which enhances a mixture of relatedness within populations and thus favors significant variance (Ritland 2000). In addition, sampled individuals were on average 15-20 m apart, an optimal distance with regard to maximizing actual variance in other woody species (Klaper et al 2001;Andrew et al 2005).…”
Section: Measurement Of Light-related Traitsmentioning
confidence: 78%
“…To provide a conservative estimate of sampling error, significance of heritability estimates was determined by bootstrapping over individuals (see Andrew et al 2005 for a comparison of different approaches). Heritability estimates were deemed significant if 95% of the bootstrapped values (n = 100) were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-scale spatial autocorrelation was observed among FPC concentrations of each species considered. FPC concentrations are highly heritable in Eucalyptus (Andrew et al 2005), and Andrew et al (2007) showed in E. melliodora that strong spatial autocorrelation in FPC concentrations overlaid a highly congruent spatial structure in genetic variance. The strength and scale of autocorrelation observed in this study for FPCs are comparable to those in E. melliodora and those for genetic markers in Tasmanian E. globulus (Skabo et al 1998), and are probably largely a product of isolation by distance (Heywood 1991).…”
Section: Discussionmentioning
confidence: 98%
“…nutrient availability (Muzika 1993), water stress (Delfine et al 2005), atmospheric CO 2 concentrations (Peñuelas et al 1997), seasonality and temperature (Emara and Shalaby 2011;Peñuelas et al 1997), herbivory (Paré and Tumlinson 1999), mediated by methyl jasmonate (Martin et al 2003) (but not eucalypts (Henery et al 2008). However, in all woody species that have been examined to date, the genetic component of variation (expressed as the narrow sense heritability) has, without exception, been high (h 2 =0.6-0.9) (Andrew et al 2005(Andrew et al , 2007Doran and Matheson 1994;Franklin and Snyder 1971;Han and Lincoln 1994;Hanover 1966aHanover , 1966bO'ReillyWapstra et al 2011;Rockwood 1973;Squillace 1971). High heritability has been observed for specific terpenes e.g.…”
Section: Variation In Terpene Yield and Heritability Of Variationmentioning
confidence: 99%
“…High heritability has been observed for specific terpenes e.g. foliar 1,8-cineole concentrations in Eucalyptus kochii (Barton et al 1991); and Eucalyptus melliodora (Andrew et al 2005), as well as total foliar terpene concentrations in Eucalyptus camaldulensis (Doran and Matheson 1994) and Melaleuca alternifolia (Doran et al 2006). The high heritability and large variation of foliar terpene concentrations in Myrtaceae raises a number of questions: How and why are foliar terpene concentrations so variable?…”
Section: Variation In Terpene Yield and Heritability Of Variationmentioning
confidence: 99%